2012
DOI: 10.1002/14651858.cd004399.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Medical versus surgical interventions for open angle glaucoma

Abstract: Primary surgery lowers IOP more than primary medication but is associated with more eye discomfort. One trial suggests that visual field restriction at five years is not significantly different whether initial treatment is medication or trabeculectomy. There is some evidence from two small trials in more severe OAG, that initial medication (pilocarpine, now rarely used as first line medication) is associated with more glaucoma progression than surgery. Beyond five years, there is no evidence of a difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 70 publications
1
118
0
2
Order By: Relevance
“…NICE guidelines have recommended that patients who present with advanced glaucoma should be offered primary glaucoma surgery. 10 A recent systematic review comparing primary medical vs surgical treatment for glaucoma 11 concluded that further randomised controlled trials of current medical treatments compared with surgery are required in people with advanced glaucoma. 11 A randomised, prospective clinical trial, comparing primary medical with primary surgical treatment in patients presenting with advanced glaucoma is thus warranted.…”
Section: Introductionmentioning
confidence: 99%
“…NICE guidelines have recommended that patients who present with advanced glaucoma should be offered primary glaucoma surgery. 10 A recent systematic review comparing primary medical vs surgical treatment for glaucoma 11 concluded that further randomised controlled trials of current medical treatments compared with surgery are required in people with advanced glaucoma. 11 A randomised, prospective clinical trial, comparing primary medical with primary surgical treatment in patients presenting with advanced glaucoma is thus warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent Cochrane study, Burr et al (2) reviewed the findings of four randomized controlled trials that had compared medical therapy and trabeculectomy in adults with open-angle glaucoma (n=888). In corroboration with the findings of the present study, they concluded that primary trabeculectomy is superior to primary medical therapy in decreasing IOP.…”
Section: Discussionmentioning
confidence: 99%
“…The exact rate in eyes with medical therapy, however, is unknown. As mentioned above, there is currently a lack of sufficient data from recent studies of newer medications and surgical techniques for glaucoma (2) , with many previous reports using flawed methodologies (5) and varying follow-up periods as well as employing different criteria to define success (6) , potentially underlying the heterogeneity in reported results. Although the efficacy of medical therapy and trabeculectomy in achieving endpoint desirable IOP did not differ significantly in the present study, the rate of failure in the medical group, i.e., the number of cases that eventually needed trabeculectomy, was still high (34%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that surgical intervention lowers IOP more effectively, but surgery is also associated with more complications (Burr et al. 2012), and thus it is relevant to search for more efficient strategies for reducing IOP that can help avoid having to resort to surgery. To our knowledge, no studies focused on IOP reduction have compared the conventional approach of stepwise treatment escalation with a more radical non‐surgical approach such as that used in the GITS.…”
Section: Introductionmentioning
confidence: 99%